Experimental learning in Sciences: getting the lab inside the classroom using the Web - de Almeida, A.; Fernandes, J.; Pascoal, M.; Pereira, S. (ICALT 2009, the 9th IEEE International Conference on Advanced Learning Technologies, 2009)
Providing authentic learning experiences by tasks based on real data is expected to result in cognitive as well as motivational benefits for students. Students' abilities to transfer what they have learned to new situations can help teachers to evaluate and improve their instruction. Under these premises, information and communication technologies are an important instrument in education and proved that well used can enhance learning and effectively motivate students towards science subjects. Technology can be used to help meet the challenges of establishing effective learning environments by bringing real-world problems into classrooms. This paper presents an experiment on learning through investigation using a Website and activities under a unifying scientific theme and realistic environment and the reasons why we expect that a broader and more adequate platform can help to bring real science learning inside the future classroom and serve as a motivating aspect to young students to turn sciences, and mathematics in particular, likeable subjects.